Insect succession and changes in the soil pH and electrical conductivity associated with decomposing pig carcasses on the Table Mountain National Park of the Western Cape Province of South Africa - Adetimehin, Adeyemi (Department of Pathology, 2024)
The establishment of region-specific baseline data on carrion-associated entomofauna and changes in the chemistry of carrion-impacted soil is crucial in the application of forensic entomology and soil chemistry in post-mortem interval estimations. However, within the Western Cape Province of South Africa, and specifically, the Table Mountain region, no studies on carrion-associated entomofauna have been published. Also, no studies in South Africa have investigated how the changes in carrion-impacted soil chemistry can be used in post-mortem interval estimations. Therefore, to establish baseline carrion entomofauna data, this study investigated the insect assemblages associated with decomposing neonate pig carcasses, alongside the impact of carcass decomposition on soil, carcass skin, and larval mass(es) chemistry, on a monthly temporal scale across the spring, summer, autumn and winter seasons. Secondly, in line with the quest for forensic relevance as evidenced by the observations from local forensic cases within the Province, this study examined the similarity in the collected carrion entomofauna, soil, carcass skin and larval mass(es) chemistry data generated from the neonate pig studies, with those generated from singly deployed adult pig carcasses across the winter and summer seasons. Thirdly, to further establish the forensic relevance of the entomofauna data generated from experimental studies, this study examined the insect species documented in forensic entomological reports of actual forensic cases within the Western Cape Province and compared the data therein with those generated from field studies using neonate and adult pig carcasses. A total of twenty-four neonate pig carcasses (two for each monthly trial) were used to generate baseline data on carrion-associated entomofauna and changes in soil pH and electrical conductivity, carcass skin and larval mass(es) in each month across the spring, summer, autumn, and winter seasons, between August 2020 to September 2021. Similar data were collected over the winter and summer seasons respectively using two adult pig carcasses (one for each seasonal trial) between June 2022 to January 2023. The neonate pig carcasses decomposed twice as fast in the summer season when compared to the spring and autumn seasons, and four times faster than those deployed in the winter season. The adult pig carcass deployed in the summer season decomposed approximately eight times faster than that deployed in the winter season.